2009
DOI: 10.1063/1.3236579
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced current and cathodoluminescence study of dislocation arrays in 4H-SiC homoepitaxial layers

Abstract: Cathodoluminescence and electron beam induced current investigations of stacking faults mechanically introduced in 4H-SiC in the brittle domain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[7][8][9][10][11] Since SiC is a promising wide-bandgap semiconductor aimed at highpower, high-frequency, and high-temperature applications, many investigations of the SFs are related to the devices ͑p-i-n diodes͒, such as the following aspects: ͑i͒ the degradation of SiC devices; 12,13 ͑ii͒ the nucleation sites of the SFs; [14][15][16] ͑iii͒ the driving force for the SF expansion under forward bias stressing; [17][18][19] ͑iv͒ partial dislocations ͑PDs͒ bounding the SFs 20-22 and ͑v͒ theoretical calculation of the electronic state of the SFs. [23][24][25] However, the fundamental/ intrinsic properties of the SFs in SiC have not been clarified very well.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Since SiC is a promising wide-bandgap semiconductor aimed at highpower, high-frequency, and high-temperature applications, many investigations of the SFs are related to the devices ͑p-i-n diodes͒, such as the following aspects: ͑i͒ the degradation of SiC devices; 12,13 ͑ii͒ the nucleation sites of the SFs; [14][15][16] ͑iii͒ the driving force for the SF expansion under forward bias stressing; [17][18][19] ͑iv͒ partial dislocations ͑PDs͒ bounding the SFs 20-22 and ͑v͒ theoretical calculation of the electronic state of the SFs. [23][24][25] However, the fundamental/ intrinsic properties of the SFs in SiC have not been clarified very well.…”
mentioning
confidence: 99%
“…EBIC is also a useful technique for the in situ study of the dislocation motion or reaction (Chen et al, 2008b(Chen et al, , 2009. Figure 35 shows the EBIC images depicting the dissociation of a BPD in 4H-SiC under e-beam irradiation (Chen et al 2008b).…”
Section: Figure 33mentioning
confidence: 99%
“…The formation of SFs by dissociating basal plane dislocations (BPDs) is often observed under forward bias stressing. 4,5) Recently, Electron-beam-induced current (EBIC) and cathodoluminescence (CL) study on 4H-SiC have shown that BPDs are easily dissociated into two partial dislocations with a SF between them under the electron-beam irradiation. 6) In this paper, we report a study on the atomic-and electronic-structure of a dislocation loop and a stacking fault in 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%